(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was designed to investigate the hypoglycemic and anti-diabetic potential of Oncocalyx glabratus. The extracts and fractions of plant were administrated orally to mice at a dose of 400 mg/kg. The hypoglycemic effect, glucose tolerance test and lipid profile were assessed in treated mice, compared with normal, diabetic and standard drug treated mice. In the hypoglycemic and anti-diabetic study the extracts and fraction reduced blood glucose level and achieved the significant value (p<0.001). The glucose tolerance test was performed in mice loaded with 3 g/kg glucose solution. n-Hexane extract and water fraction reduced the glucose level significantly (p<0.001) after 60, 90 and 120 min conversely ethyl acetate and methanol extracts showed the significant (p<0.001) reduction after 90 and 120 min. Ethyl acetate and methanol extracts showed substantial changes in biochemical parameters, compared to the standard drug. So, the study suggested the hypoglycemic and anti-diabetic activity of the title plant.